CLINICAL OUTCOMES AND ADVERSE DRUG REACTIONS IN COVID-19 PATIENTS TREATED WITH HYDROXYCHLOROQUINE AND AZITHROMYCIN ALONE OR COMBINED - Rathi, H.; Rathi, P.; Biyani, M. (International Journal of Medicine and Medical Research, 2021)
Background. Use of Hydroxychloroquine with or without Azithromycin is repurposed in SARS-CoV-2 in the absence of definitive treatment. Objective. To evaluate the association between the use of Hydroxychloroquine and Azithromycin when given alone or in combination on clinical outcomes and adverse drug reactions among lab confirmed SARS CoV-2 positive patients admitted in a COVID tertiary care hospital of a University Medical college. Methods. a retrospective observational comparative study was conducted. COVID-19 positive patients admitted in study hospital for management of COVID-19 were enrolled into the study. The patients were categorized into 4 treatment groups based on having received the following treatment during hospitalization: (A) Hydroxychloroquine with Azithromycin, (B) Hydroxychloroquine without Azithromycin (Hydroxychloroquine alone), (C) Azithromycin alone, and (D) Neither drug, defined as no receipt of either Hydroxychloroquine or Azithromycin in the record; other medications may have been dispensed. Results. 800 patients were enrolled. Mean±Standard deviation of duration of hospital stay (in days) for study Group A was 11.37±7.11, for Group B was 8.37±4.77, for Group C was 18.22 ± 5.69 and for Group D was 6.12±2.97. Mortality in Group A was 29.74%, Group B – 33.16%, Group C – 0% and in Group D – 1.32%. Conclusion. Among hospitalized patients with COVID-19 treatment, Group C was associated with good clinical outcome. However, the interpretation of these findings may be limited by the observational design.